Vínculo no trabalho cotidiano entre equipe de saúde bucal e usuários - Ludmila Brito e Melo Rocha (2014)
Case study with qualitative approach based on Quotidian Comprehensive Sociology that aimed to understand the bond between professional and users on quotidian of oral health teams in the Primary Health Care, from the perspective of users and workers involved. The studys scenario was the oral health service of a small city located in the metropolitan area of Belo Horizonte-MG. The study involved three oral health teams four dentists, two oral health assistants and two oral health technicians , eight users, besides three nurses as key informants; all those subjects live quotidian routines within the citys oral health service and make up a social and special reality. Data gathering was obtained through non-participating observation by using a field diary and interview with the use of semi-structured scripts. We performed triangulation technique of instruments that connected the results of the interviews and the observations. The data was submitted to a thematic content analysis and organized in two empirical categories, respectively subdivided into two and for subcategories: 1. The bonds within the bond: polysemy in the therapeutic relationship a) The bond becoming the organizer on quotidian work: beginning, mean and objective. b) Complexity (un) reachable: bond as a perfect meeting (or nearly always). From this category and its subcategories, we may assume that the bond can have many sides, such a guideline to be used to reach therapeutic success up to the goal itself; conceptual entity yet but of virtuous, delicate and difficult consolidation; and a phenomenon that may be undesirable depending on its meaning. 2. The bond within the work quotidian routine and the work quotidian routine in the bond: conditioning elements and determiners. a) A look into the professionals unicity b) Oral health teams: annex or part of health teams? Protagonists or supporting actors? c) Who, how and what in the work quotidian routine of oral health teams d) Still a quite narrow accesss door: advances yes, but not enough. The second category, and its subcategories, represents the elements that show influence, positive or negative, in the consolidation of the bond on the therapeutic relationship. Among them: the profile and attitude of involved professionals; the (in)existence of the oral health teamss protagonism among the health teams; characteristics related to the work quotidian routine itself and the model of attention it mirrors; besides restrictions / and the remaining accesss gaps to oral health services. The results suggest that the bond consolidates in a peculiar fashion while trust and closeness ties grow between professionals and users, in spite of the limitations imposed by reality. The citys regional reality refers to in this work seems to be a portrait of so many other Brazilians cities; and leads us to believe that one of the possible outcomes of that study is that others may see, in our results and interpretations, features likely to be similar to their own scenarios. It is also expected that these results may offer insights on the planning, management and evaluation processes of the oral health in the Primary Health Care.